2020
DOI: 10.3390/ijms21062246
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Expression Pattern and Antiviral Activities of Mx Gene in Chinese Giant Salamander, Andrias davidianus

Abstract: Mx, Myxovirus resistance is an important interferon-stimulated protein that mediates antiviral responses. In this study, the expression and activities of Chinese giant salamander, Andrias davidianus Mx gene, AdMx, were investigated. The AdMx cDNA sequence contains an open reading frame (ORF) of 2112 nucleotides, encoding a putative protein of 703 aa. Meanwhile, AdMx possesses the conserved tripartite GTP binding motif and a dynamin family signature. qRT-PCR analysis revealed a broad expression of AdMx in vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Mx proteins are against many RNA and DNA viruses [ 25 , 26 ]. A recent study shows that overexpressed Andrias davidianus Mx (AdMx) in the Chinese giant salamander’s muscle cells significantly reduced Chinese giant salamander iridovirus (GSIV) replication indicating that the Mx shows potential antiviral properties against iridoviruses [ 27 ]. In the present study, the localization of Mx1 protein in exosomes was identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mx proteins are against many RNA and DNA viruses [ 25 , 26 ]. A recent study shows that overexpressed Andrias davidianus Mx (AdMx) in the Chinese giant salamander’s muscle cells significantly reduced Chinese giant salamander iridovirus (GSIV) replication indicating that the Mx shows potential antiviral properties against iridoviruses [ 27 ]. In the present study, the localization of Mx1 protein in exosomes was identified.…”
Section: Discussionmentioning
confidence: 99%
“…MFF-1 cells were grown and maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum (FBS) at 27 °C in 5% CO 2 [ 28 ]. The MFF-1 cell line was highly susceptible to the ISKNV [ 27 ]. In our lab, this cell line is used to ISKNV passage and isolate from disease-infected fish [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Mx proteins have been used as hallmarks of interferon production and viral infection in vertebrates [17,32,33]. They have broad antiviral activity, such as prevention of viral RNA synthesis and protein expression, and they can inhibit the replication of many types of viruses, including Chinese giant salamander iridovirus, hepatitis B virus, reoviruses, and nodavirus [34][35][36][37][38]. Chen et al demonstrated that gMx proteins could inhibit the synthesis of nodavirus RNA-dependent RNA polymerase, bind to the nodavirus coat protein, and inhibit viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…IRF3 expression was increased in the spleen at 3 hpi (28). Type I IFN transcript levels were upregulated in peripheral blood leukocytes at 12 hpi, while Mx transcripts levels were upregulated in the spleen at 6 hpi and in the kidney at 12 hpi (70,71). Inflammatory genes such as TNF-a and IL-1b were significantly induced in the spleen at 3 dpi and in the kidney at 7 dpi, while the macrophage migration inhibitor (mif) gene was induced in the spleen at 3 dpi and in the kidney at 12 dpi.…”
Section: Innate Immune Response To Gsivmentioning
confidence: 97%
“…Although LGP2 lacks CARD domain in other vertebrate (69), the structure signature of AdLGP2 has not been investigated. The RLR activation pathway induces IFN regulatory factor 3 (IRF3) regulated type-I interferon response and subsequently stimulates the production of IFN-stimulated genes (ISGs) including ISG15 and the Myxovirus resistance (Mx) gene, which has been characterized in the Chinese giant salamander (28,(69)(70)(71). Further characterization of the RLR pathway in A. davidianus should now be undertaken and in particular the absence of adapter IPS-1 will have to be confirmed.…”
Section: Innate Immune Systemmentioning
confidence: 99%